(untitled) (Bangladesh Journal of Public Administration, 2020)
The purpose of this study is to analyze the causal relationship of external debt and balance of payment with foreign direct investment (FDI) in Bangladesh for the period of 1980 to 2017 through the application of Johansen Cointegration technique, Vector Error Correction Model (VECM), and Granger Causality approach. Results of cointegration and VECM indicate a significant long-run relationship between dependent (FDI) and independent variables (external debt and balance of payment). External debt is found to have a significant negative impact on FDI in the long-run, but it is found insignificant in the short-run. In contrast, the balance of payment has a significant positive effect on FDI both in the long-run and short-run. Results of the Granger causality test reveal that there exists bidirectional short-run causality between the balance of payment and FDI; that is, both the balance of payment and FDI affect each other. But no unidirectional or bidirectional short-run causality is found between external debt and FDI. Keywords: FDI, external debt, balance of payment, cointegration, VECM, causality